2010
DOI: 10.1007/s10532-010-9391-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ozone for preventing fungal influenced corrosion of reinforced concrete bridges over the River Nile, Egypt

Abstract: Fungal influenced corrosion (FIC) of some corroded sites in three selected bridges [Embaba bridge (E-bridge), Kasr al-Nile-bridge (K-bridge) and University bridge (U-bridge)] located over the River Nile in Egypt were investigated. Six fungal species, belong to 12 fungal genera, were isolated from the corroded reinforced concrete of the three tested bridges. Fourier transform infrared spectroscopy (FTIR) was screened for the most dominant fungal species (Fusarium oxysporium) which showed in all tested bridges t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The shifting wave numbers and the new bond formation that appeared previously in (Table 6) through the functional groups of VAC inhibitor on the metal surface supporting the interaction between the active constituents of VAC inhibitor and the metal surface. The presence of extract components that containing nitrogen & oxygen heteroatoms together with Л electron clouds over benzene rings and other double and triple bonds finally confirmed that, those donor atoms and bonds act as active centers that suppresses the redox reaction by making a protective film from VAC solution through its mixed nature in adsorption so as to, inhibit severe corrosion which takes place with 1M HCl on the CS 1018 surface [56][57][58][59][60][61] .…”
Section: Atomic Force Microscopy (Afm) Testsmentioning
confidence: 84%
“…The shifting wave numbers and the new bond formation that appeared previously in (Table 6) through the functional groups of VAC inhibitor on the metal surface supporting the interaction between the active constituents of VAC inhibitor and the metal surface. The presence of extract components that containing nitrogen & oxygen heteroatoms together with Л electron clouds over benzene rings and other double and triple bonds finally confirmed that, those donor atoms and bonds act as active centers that suppresses the redox reaction by making a protective film from VAC solution through its mixed nature in adsorption so as to, inhibit severe corrosion which takes place with 1M HCl on the CS 1018 surface [56][57][58][59][60][61] .…”
Section: Atomic Force Microscopy (Afm) Testsmentioning
confidence: 84%
“…(II) Decrease in the intensity band of water absorption around (1,640 cm −1 ) and decrease in O‐H stretching band around (3,300–3,400 cm −1 ); this was due to the water loss and the dry storage conditions. (III) Decrease in C=C stretching band around (1,508 cm −1 ) due to the loss of lignin according to fungal degradation (Geweely, 2011; Kubovský et al, 2020). (IV) Decrease in C‐O‐C stretching bands around (1,160 cm −1 ); this indicates the advanced cellulose chain breaking and the depolymerization occurrence (Kubovský et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Filamentous fungi are known to highly biodeteriorate materials [62]. These fungi have an invasive growth that many times manages to break the material on which they grow and at the same time release large amount of acids that favour corrosion processes [63]. Besides, Aspergillus as is one of the most common genera associated with biodeterioration of coatings and paints [64].…”
Section: Tablementioning
confidence: 99%